Ultimate Guide to Email Marketing for Business. - Gunelius, Susan (Entrepreneur Press, 2018)
Ultimate Guide to Email Marketing for Business is a complete system to help entrepreneurs and small business owners leverage the power of email to build a business by attracting leads and turning them into customers, brand ambassadors, and revenue generators.